The Effectiveness of Visit Lombok Sumbawa (VLS) Program in 2012-2014 to Increase Foreign Tourist in Nusa Tenggara Barat (NTB) Province (Case Study Dinas Kebudayaan dan Pariwisata (Disbudpar) and Bad - Handri Harry (IPEM 15 UMY 271, 2015)
*271